Pakistan Army Green Book 2010 : Information Warfare - Pakistan Army; Editor-in-Chief : Khushnud Iqbal, Brig.; Co-Editor: Paracha, Wajid Qayum Col.; Editor: Mirza, Saqib Jehangir, Col. (GHQ, Rawalpindi Pakistan Army, 2010)
Content of the book are the writer's personal views and are not to be taken as official opinion/policy.
Include Tables and Illustrations.
Keywords: Pakistan Army -- Army, Pakistan -- Army Research Journal -- Research Journal, Army